2006
DOI: 10.1038/sj.bmt.1705401
|View full text |Cite
|
Sign up to set email alerts
|

Haematopoietic cell transplantation (HCT) in combination with enzyme replacement therapy (ERT) in patients with Hurler syndrome

Abstract: Hurler syndrome (MPS 1H) is the severe form of mucopolysaccharidosis type 1 (MPS 1). Haematopoietic cell transplantation (HCT) is the treatment of choice, but carries a high incidence of graft failure and morbidity. The use of enzyme replacement therapy (ERT) might improve the clinical signs and symptoms before HCT, resulting in less transplantation-related complications. Moreover, clearance of glycosaminoglycans (GAG's) from the bone marrow might improve engraftment. Twenty-two patients with MPS 1H received o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
73
0
5

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(78 citation statements)
references
References 20 publications
0
73
0
5
Order By: Relevance
“…5 The methylated disaccharide derived from the NA domains of HS behaved similarly to that derived from CS. The presumed dimeric product derived from the NS domain yielded predominantly a sodiated molecular ion at m/z 406 in the mass spectrum of the methanolysate HS (data not shown).…”
Section: Analysis Of Gags In Csf By Uplc-ms/msmentioning
confidence: 86%
“…5 The methylated disaccharide derived from the NA domains of HS behaved similarly to that derived from CS. The presumed dimeric product derived from the NS domain yielded predominantly a sodiated molecular ion at m/z 406 in the mass spectrum of the methanolysate HS (data not shown).…”
Section: Analysis Of Gags In Csf By Uplc-ms/msmentioning
confidence: 86%
“…No treatment is currently available for MPS IIIB. The therapies currently available for other MPS disorders, such as bone marrow transplantation 4,5 and recombinant enzyme replacement therapy (ERT), 6,7 are not recommended for MPS III. This is due to the fact that the CNS pathologies in MPS III are global, and neither the peripherally delivered bone marrow stem cells nor the recombinant enzymes can be efficiently delivered to the CNS through the blood-brain barrier (BBB).…”
Section: Introductionmentioning
confidence: 99%
“…Supplementary ERT before HSCT rapidly reduces upper airway obstruction, and improves cardiorespiratory capacity thereby improving patient fitness for HSCT (Grewal et al 2005;Cox-Brinkman et al 2006;Muenzner et al 2009;Wynn et al 2009;Tolar et al 2008;Bijarnia et al 2009;Clarke et al 2009). We have demonstrated that a treatment regimen of ERT combined with HSCT in our patient with MPS VI provided similar benefit.…”
Section: Discussionmentioning
confidence: 99%